Andrée Chedid, Vénus Khoury-Ghata, and Martine Broda - Marie-Claire Bancquart (Studies in 20th & 21st Century Literature, 2002)
I would like to present three poets who are very different in age and writing style, Andrée Chedid, Vénus Khoury-Ghata and Martine Broda, in order to show the diversity of paths opened up by a women's poetry to which criticism and anthologies still give too small a place in France...
Keywords: poets; poetry; Andrée Chedid; Vénus Khoury-Ghata; Martine Broda; women& #x27; s poetry; France; French poetry